2016
DOI: 10.1007/s00464-016-4826-9
|View full text |Cite
|
Sign up to set email alerts
|

Age is highly associated with stereo blindness among surgeons: a cross-sectional study

Abstract: Approximately one in ten medical doctors in general surgery, gynecology, and urology were stereo blind with an increasing prevalence with age. This is relevant since stereo blind surgeons will not benefit from the implementation of 3D laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 38 publications
3
22
0
Order By: Relevance
“…First, we did not take into consideration the unsuitability of each participant for stereo vision. Several studies about 3D indicated that there are some people who have disadvantages of stereo vision, such as stereo blindness [ 16 , 17 ], or the side effects (feeling discomfort, headache, or sickness) using a 3D monitor [ 18 ]. However, each participant in this study improved their performance and did not feel any discomfort or sickness as side effects by 3D during the trial.…”
Section: Discussionmentioning
confidence: 99%
“…First, we did not take into consideration the unsuitability of each participant for stereo vision. Several studies about 3D indicated that there are some people who have disadvantages of stereo vision, such as stereo blindness [ 16 , 17 ], or the side effects (feeling discomfort, headache, or sickness) using a 3D monitor [ 18 ]. However, each participant in this study improved their performance and did not feel any discomfort or sickness as side effects by 3D during the trial.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity to binocular disparity information varies substantially in the general population, with two‐thirds of individuals having good to excellent stereoacuity (so‐called ‘haves’) and the remainder having moderate to poor stereoscopic perception (so‐called ‘have‐nots’). A recent cross‐sectional study of surgeons suggests that 10 per cent may be ‘stereoblind’. Binocular disparity information is also affected by viewing distance.…”
Section: Introductionmentioning
confidence: 99%
“…recommendations that 3D systems should be utilised in the clinical setting to decrease operating times [12]. However, these systems are expensive, and around ten percent of surgeons cannot perceive stereoscopic depth [13,14]. Furthermore, no clinical trials have investigated whether 3D systems have performance benefits over ultra-high-definition ('4K') laparoscopic imaging-a new two-dimensional technology with four times the number of pixels of HD, which potentially provides stronger monocular depth-perception cues.…”
mentioning
confidence: 99%